1997
DOI: 10.1093/ndt/12.8.1586
|View full text |Cite
|
Sign up to set email alerts
|

Renal function and oxygen consumption during bacteraemia and endotoxaemia in rats

Abstract: Our data indicate that in rat models of septic shock renal failure is not caused by cortical hypoxia or a shortage of cellular energy supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 5 publications
6
23
0
Order By: Relevance
“…Prior studies have shown that in the first 1-4 hours after intravenous endotoxin exposure, intrarenal oxygen consumption is unchanged despite reduced delivery (35)(36)(37). Our results at a later time may reflect a transition to mitochondrial dysfunction as endotoxemia progresses.…”
Section: Discussionsupporting
confidence: 43%
“…Prior studies have shown that in the first 1-4 hours after intravenous endotoxin exposure, intrarenal oxygen consumption is unchanged despite reduced delivery (35)(36)(37). Our results at a later time may reflect a transition to mitochondrial dysfunction as endotoxemia progresses.…”
Section: Discussionsupporting
confidence: 43%
“…Of these articles, 52 (38.0%) showed a decreased RVR [25, 28, 30, 31, 32, 33, 34, 36, 45, 46, 47, 51, 52, 53, 58, 62, 63, 68, 69, 70, 71, 72, 73, 74, 75, 78, 84, 85, 87, 92, 95, 98, 99, 100, 101, 109, 111, 112, 114, 115, 120, 122, 124, 125, 126, 130, 131, 135, 143, 144, 154, 155], 16 (11.7%) an unchanged RVR [23, 29, 35, 37, 60, 64, 80, 97, 106, 108, 110, 113, 116, 119, 140, 145,] and 69 (50.3%) an increased RVR [20, 21, 22, 24, 26, 27, 38, 39, 40, 41, 42, 43, 44, 48, 49, 50, 54, 55, 56, 57, 59, 61, 65, …”
Section: Resultsmentioning
confidence: 99%
“…We found 56 experiments performed in small animals [20, 24, 26, 27, 39, 42, 43, 44, 55, 57, 58, 59, 62, 63, 64, 67, 68, 72, 77, 79, 81, 82, 87, 88, 89, 90, 93, 94, 96, 97, 99, 100, 103, 104, 105, 110, 116, 120, 121, 122, 129, 132, 133, 134, 137, 138, 139, 141, 142, 143, 147, 148, 149, 150, 151] and 81 performed in large animals [21, 22, 23, 25, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 40, 41, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 56, 60, 61, 65, 66, 69, 70, 71, 73, 74, ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One proposed hypothesis is an increased leakiness of the proximal tubular epithelium resulting in sodium back-flow towards the tubular lumen as well as equal work for less sodium reabsorption. 52 …”
Section: The Kidney In Sepsismentioning
confidence: 99%